Isolasi Selulosa dari Tongkol Jagung melalui Delignifikasi Ultrasonik - Mustofa, Arya; Susilowati, Fifit; Suprianti, Lilik; Billah, Mu’tasim (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Corncob was chosen as a raw material due to its high lignocellulose content, including 36.4% cellulose. The delignification process was performed using alkaline treatment with NaOH, enhanced by ultrasonik irradiation, creating cavitation that helps break lignin bonds, shortens processing time, and increases cellulose yield. The ultrasonic assistance aims to provide an optimal solution for lignin processing. Variables tested included ultrasonic power (80-120 watts) and delignification time (50-70 minutes). The study results indicated that both ultrasonic power and duration influenced cellulose content, with the highest yield of 66.08% achieved at 110 watts and 60 minutes. FTIR analysis showed a reduction in peak intensity, indicating lignin reduction, while SEM analysis confirmed significant surface morphology changes after delignification. In conclusion, the ultrasonic delignification method proved effective in separating cellulose from corncob, yielding better results and more efficient processing times, demonstrating the potential of ultrasonic technology in the biomass processing industry for more environmentally friendly and energy-efficient cellulose production. Further studies are recommended to optimize process conditions and evaluate industrial-scale applications.